Literature Review : Pendekatan Diagnosis dan Tata Laksana Rhinitis Atrofi (Ozaena) - Tita Aulia Putri (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Atrophic rhinitis or ozena is a chronic infection of the nasal cavity characterized by progressive atrophy of the nasal mucosa and turbinate bones accompanied by the formation of foul-smelling nasal crusts. This condition is more commonly found in females, particularly during puberty, and is frequently associated with populations of low socioeconomic status and poor environmental sanitation. The exact etiology of atrophic rhinitis remains unclear; however, several factors are believed to contribute, including chronic infection by *Klebsiella ozaenae*, vitamin A and iron deficiency, chronic sinusitis, hormonal imbalance, collagen diseases, trauma, and genetic predisposition. Common clinical manifestations include nasal obstruction, thick greenish nasal discharge, crust formation, epistaxis, anosmia, and *foetor ex nasi*, which is often more noticeable to people around the patient. Anterior rhinoscopy typically reveals widened nasal cavities, turbinate atrophy, thin and dry nasal mucosa, as well as purulent secretions and greenish crusts. Diagnosis is established through history taking, ENT physical examination, and supporting investigations such as microbiological culture, histopathological examination, radiological imaging, and paranasal sinus CT-scan. Management may be conservative with antibiotics, nasal irrigation, nasal drops, vitamin A supplementation, and iron preparations, or surgical in severe cases or those unresponsive to conservative therapy.